Analysis of agricultural and hydrological drought periods by using non-homogeneous Poisson models: Linear intensity function. (February 2020) - Ellahi, Asad; Almanjahie, Ibrahim M.; Hussain, Tajammal; Hashmi, Muhammad Zaffar; Faisal, Shahla; Hussain, Ijaz
Abstract: The abnormal behavior of the precipitation in recent years has caused shrinkage of water supplies, floods and rising seas and rivers in all over the world. Pakistan is one of those countries which are highly effected from this abnormal behavior. In this paper, we utilized the concept of drought indices for the calculation and exploratory analysis of the agricultural and hydrological droughts with its intensities at multiple locations. The concept of point processes to analyze the drought periods at different locations was also investigated. The 3-months and 12-months Standardized Precipitation Index (SPI) were used to calculate the agricultural and hydrological drought events. The accumulated number of agricultural and hydrological drought events are calculated by considering the threshold of −1.0, and analyzed the drought periods by using Non-Homogeneous Poisson Process (NHPP). The parameters of the model were estimated by using Bayesian approach with Gibbs sampling under Markov Chain Monte Carlo (MCMC) algorithm. The results revealed that SPI provides the better and detailed structure of the agricultural and hydrological droughts with different intensity levels at multiple locations. The study showed that every region of Pakistan was significantly influenced by the agricultural and hydrological droughts with different intensity levels and magnitudes. The NHPP was found to be better in the assessment and analysis of drought events occur during a specific period. The findings of this study can be an important reference for the policymakers and government to take decisions in advance for sustainable environmental management in Pakistan. Highlights: Agricultural and hydrological drought periods Pakistan Non-homogeneous Poisson models Pakistan was influenced by agricultural and hydrological droughts The NHPP performed better in the assessment and analysis of drought